Decentralization and Citizen Participation in the Provision of Local Public Services - Adelaide de Vasconcelos; Erwin Erwin; Widya Fitriana (Journal of World Science, 2026)
This research analyzes the impact of decentralization policies on the quality of local public services in the road infrastructure sector and evaluates the role of citizen participation in improving road accessibility in Ermera Municipality, Timor-Leste. Decentralization is viewed as a strategy to enhance service delivery and democratic legitimacy through community involvement, yet its effectiveness is often limited by institutional capacity, fiscal dependence on the central government, and weak citizen participation mechanisms. A qualitative case study approach was employed, with data collected through in-depth interviews with local officials, community leaders, and residents, as well as field observations and document analysis. Thematic analysis was used to process the data, ensuring validity through triangulation. The findings show that while decentralization has increased local government authority in road planning and implementation, fiscal constraints, lack of transparency, and weak coordination limit its effectiveness. Citizen participation has a positive impact on identifying needs and supporting project execution, but it remains largely consultative and insufficiently institutionalized, particularly in monitoring and evaluation. In conclusion, decentralization and citizen participation complement each other in improving local public services. Strengthening the technical and fiscal capacity of local governments and institutionalizing citizen involvement at all stages is crucial for achieving inclusive, responsive, and sustainable road infrastructure. The study offers strategic implications for decentralization reforms in developing countries.